2023
DOI: 10.1080/15476286.2023.2195731
|View full text |Cite
|
Sign up to set email alerts
|

Cross-kingdom small RNA communication between plants and fungal phytopathogens-recent updates and prospects for future agriculture

Abstract: Small RNAs (sRNAs) are short non-coding regulatory RNA sequences that silence the complementary expressive transcripts through an endogenous RNA mediated interference mechanism (RNAi). These sRNAs typically move through plasmodesmata and phloem in plants to support disease resistance, and also through septal pores and vesicles in fungi to act as effector of pathogenicity. Notably, recent reports have shown the occurrence of a bidirectional trafficking of these sRNAs between the host plants and the attacking fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 86 publications
0
1
0
Order By: Relevance
“…Host-induced gene silencing (HIGS) is a novel concept based on the cross-kingdom RNAi mechanism. HIGS involves overexpressing insect-targeted double-stranded RNAs (dsRNAs) or artificial miRNAs in host plants to specifically block the expression of feeding-and survival-related genes in target pests and pathogens (Huang et al, 2019;Jiang et al, 2023;Mahanty et al, 2023) (Figure 1A). A growing number of studies have demonstrated the successful application of HIGS in crop protection (Escobar et al, 2001;Seemanpillai et al, 2003;Zha et al, 2011;Van et al, 2014;Coleman et al, 2015;Shivakumara et al, 2017;Panwar et al, 2018).…”
Section: Application Of Cross-kingdom Rnai In Crop Protectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Host-induced gene silencing (HIGS) is a novel concept based on the cross-kingdom RNAi mechanism. HIGS involves overexpressing insect-targeted double-stranded RNAs (dsRNAs) or artificial miRNAs in host plants to specifically block the expression of feeding-and survival-related genes in target pests and pathogens (Huang et al, 2019;Jiang et al, 2023;Mahanty et al, 2023) (Figure 1A). A growing number of studies have demonstrated the successful application of HIGS in crop protection (Escobar et al, 2001;Seemanpillai et al, 2003;Zha et al, 2011;Van et al, 2014;Coleman et al, 2015;Shivakumara et al, 2017;Panwar et al, 2018).…”
Section: Application Of Cross-kingdom Rnai In Crop Protectionmentioning
confidence: 99%
“…Although allowing insects to feed on plants overexpressing exogenous dsRNA was not as effective as injecting insects directly, HIGS remains a promising pest control strategy. However, the implementation of HIGS depends on the generation of transgenic plants, which is both time-intensive and costly (Jiang et al, 2023;Mahanty et al, 2023). These limitations have so far hampered the application of HIGS to BPH control in rice.…”
Section: Application Of Cross-kingdom Rnai In Crop Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene silencing is a conserved eukaryotic homology-dependent post-transcriptional mechanism of gene expression regulation. In fungi, gene silencing controls growth, development, and virulence [125]. Gene ontology found an upregulation of gene silencing by miRNA.…”
Section: Conidial Processes Regulation By Gene Silencingmentioning
confidence: 99%
“…Plant sRNAs can also move intercellularly across plasmodesmata and systemically across the phloem, acting cell non-autonomously and can also translocate between interacting species (Zhan & Meyers, 2023). In the latter case, sRNAs are transferred bidirectionally between plant hosts and pathogenic microbes to modulate defence and virulence, a phenomenon called cross-kingdom RNAi (ckRNAi) (Göhre and Weiberg, 2023; Mahanty et al, 2023; Wang et al, 2017). ckRNAi in plant-pathogen interactions was discovered in 2013 when the necrotrophic fungus Botrytis cinerea was shown to induce silencing of host defence genes in Solanum lycopersicum and Arabidopsis thaliana ( At ) (Weiberg et al, 2013).…”
Section: Introductionmentioning
confidence: 99%